Does the Centre Hold? Public Sphere Configuration Democracy and the Quality of Political Talk in Sweden - Strandbrink, Peter (Javnost-The Public, 2024)
In the present article, key conceptual and regulative requirements for quality public democratic talk to be maintained are identified and the linguistic economy of civic conversation about common affairs in the Swedish public sphere gauged; the relationship between public talk, power, and identity is charted; and exposure and response horizons for further quality slippage with Swedens's institutional frameworks visited. A distinction between width and amp difference is introduced to separate democratically acceptable from unviable modes of conversational engagement and provide a new platform for analysing this space. Democratic history and theory is also visited, showing how cognitive moral conversation is a precondition for democratic governance. It is ultimately shown that if democratic politics wishes to remain within its remit, key ideals need safeguarding. It is concluded that the well-known challenges brought out by Levitsky & Ziblatt have not yet affected Swedish politics as they have American politics, but that risks for graver deterioration of struggling conversational and normative formats are visible.